2013
DOI: 10.1021/es401160g
|View full text |Cite
|
Sign up to set email alerts
|

Control of Heterogeneous Fe(III) (Hydr)oxide Nucleation and Growth by Interfacial Energies and Local Saturations

Abstract: To predict the fate of aqueous pollutants, a better understanding of heterogeneous Fe(III) (hydr)oxide nucleation and growth on abundant mineral surfaces is needed. In this study, we measured in situ heterogeneous Fe(III) (hydr)oxide nucleation and growth on quartz, muscovite, and corundum (Al2O3) in 10(-4) M Fe(III) solution (in 10 mM NaNO3 at pH = 3.7 ± 0.2) using grazing incidence small-angle X-ray scattering (GISAXS). Interestingly, both the fastest heterogeneous nucleation and slowest growth occurred on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
62
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 83 publications
3
62
0
Order By: Relevance
“…Here, we advance that understanding by using in situ grazing-incidence small-angle X-ray scattering (GISAXS) to measure heterogeneous nucleation and growth rates of (Ba x , Sr 1−x )SO 4 precipitated on organic films from Sr-rich solutions. As previously demonstrated, GISAXS measures nucleation and growth rates at solid-liquid interfaces with sufficient temporal and spatial resolution (18)(19)(20)(21)(22)(23)(24)(25)(26) to provide unique information about substrate-mineral interactions (24). In our recent study, a range of organic coatings (terminated with -COOH, -SH, and mixed -SH-and-COOH functional groups) were found to significantly affect the heterogeneous nucleation and growth kinetics of barite by controlling the local ion concentrations and the interfacial energies for heterogeneous barite nucleation (24).…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Here, we advance that understanding by using in situ grazing-incidence small-angle X-ray scattering (GISAXS) to measure heterogeneous nucleation and growth rates of (Ba x , Sr 1−x )SO 4 precipitated on organic films from Sr-rich solutions. As previously demonstrated, GISAXS measures nucleation and growth rates at solid-liquid interfaces with sufficient temporal and spatial resolution (18)(19)(20)(21)(22)(23)(24)(25)(26) to provide unique information about substrate-mineral interactions (24). In our recent study, a range of organic coatings (terminated with -COOH, -SH, and mixed -SH-and-COOH functional groups) were found to significantly affect the heterogeneous nucleation and growth kinetics of barite by controlling the local ion concentrations and the interfacial energies for heterogeneous barite nucleation (24).…”
mentioning
confidence: 85%
“…With the assumption of noninteracting spherical nanoparticles with lognormal distributions, the average particle sizes were calculated by fitting the 1D scattering intensity curves. All data analysis was performed with Igor Pro-6.34 (WaveMetrics), and more detailed data analysis can be found in our previous publications (19)(20)(21)(22)(23)(24)(25)(26).…”
Section: Solution Conditions For (Ba X Sr 1−x )So 4 Precipitation Amentioning
confidence: 99%
“…The specific surface areas of WS with different sizes (20,60,80, and 120 mesh) were measured by nitrogen adsorption using the Brunauer-Emmett-Teller method (V-Sorb2800). Dynamic light scattering (DLS, Zetasizer Nanoseries, Malvern Instruments) was used to measure the zeta potential values ( ) of WS particles in aqueous solutions under various pH conditions [30,31]. According to previous work, the WS particles of 0.1 g were suspended in DI water (pH was adjusted from 2 to 12 using 0.1 mol/L HCl or NaOH), and the zeta potential measurements were conducted every 1 min for 30 min.…”
Section: Adsorbent Characterizationmentioning
confidence: 99%
“…For example, Fernandez-Martinez et al 34 and Li et al 36 reported that the interfacial energies for nucleation of CaCO 3 on silicates were as low as 35-50 mJ m −2 . The overall system's interfacial energy can be affected appreciably by individual interfacial energies among nuclei, substrates, and solutions 13,33,35,36,[39][40][41] .…”
mentioning
confidence: 99%